Influence of Different Fuzzifiers on The Effect of The OFNBEE Algorithm - Dawid EWALD (Communications of International Proceedings, 2021)
The article describes a new hybrid method for bee optimisation using the arithmetic of ordered fuzzy numbers. The aim of this combination is to more realistically represent the decision-making mechanisms of bees, commonly referred to as waggle dance. The OFN notation allows to more accurately transfer the information between individuals, which contributes to the improvement of the optimisation algorithm. The article describes the fuzzy functions necessary for the new method to work, but also for the very use of OFN in other algorithms. Since there are no fuzzing methods available in the literature, a few such methods are proposed in this article. The new method also utilises the defuzzification functions, and the two most well-known of them were used for the experiment, namely Golden Ratio and Mandala Factor. The last section is a description of the new method and the results achieved by OFNBee for selected functions: Bukin N.6, Cross-in-tray, Drop Wave, Eggholder, Levy and Holder Table.
Keywords: OFNBee; fuzzifiers; OFN.